Effect of Long-Term Captopril Administration on Bone Density and Orthodontic Tooth Movement - Amir Hossein Mirhashemi; Mohammad Sadegh Ahmad Akhoundi; Elahe Ansari; Sedigheh Sheikhzadeh; Nafiseh Momeni; Ahmadreza Dehpour; Shahroo Etemad-Moghadam; Yasaman Kheirandish; Homa Farhadifard (Islamic Dental Association of Iran, 2016)
Background and Aim: Captopril is an oral angiotensin-converting-enzyme (ACE) inhibitor extensively used in the treatment of hypertension and heart failure. ACE has been suggested to function in bone cells and might therefore impact orthodontic tooth movement (OTM). Considering the controversy surrounding the effects of ACE and its inhibitors on osseous tissues, we aimed to evaluate the effect of captopril on OTM for the first time in a rat model. Materials and Methods: Orthodontic appliances were fixed between the left first molars and incisors of 30 rats divided into three groups (n=10) receiving captopril, saline or no treatment. Following sacrifice on day 21, the amount of tooth movement was measured as the distance created between the first and second molars. Bone density was assessed by lateral cephalograms on days 1 and 21 and osteoclast number, root resorption and periodontal ligament (PDL) width were analyzed histologically. One-way ANOVA followed by post-hoc test were used for statistical analysis (P<0.05) Results: OTM significantly increased in the captopril group compared to the saline and no-treatment groups (P<0.05). Bone density significantly decreased in the mandible of the captopril group from day 1 to 21 (P<0.05). No significant differences were found in the histological variables except for the significant increase in PDL width at the mesioapical aspect in the captopril group. Conclusion: The present study showed that captopril administration could lead to increased OTM and decreased bone density in rats. Further studies are suggested to clarify its exact role at the cellular and molecular levels. Key Words: Captopril, Tooth Movement Techniques, Rats